Kinerja Keuangan Koperasi Angkatan Udara Lanud Dhomber Balikpapan Berdasarkan Rasio Likuiditas, Leverage dan Profitabilitas - Kadori Haidar; Irdiansyah; Qanaya Bintang Santoso; Sutrisno (Journal of Trends Economics and Accounting Research, 2023)
Financial performance is important for every company or organization that runs a business. Good financial performance is measured from the results of financial report analysis and is given a percentage according to predetermined criteria, so that the results of the analysis can be used to develop appropriate plans and policies to achieve the vision and mission of the cooperative. The purpose of this study is to determine the movement of cooperative financial performance reporting based on liquidity, solvency and profitability ratios from 2018 to 2021. The method used in this study is descriptive and quantitative. The results of this study indicate that the financial reporting results of the Dhomber Air Force cooperative are very safe or strong in terms of liquidity and leverage. The cooperative's liquidity ratio shows good results because the cooperative's ability to pay is very high where each short-term debt is guaranteed by several assets. While the leverage analysis shows. As for profitability, the higher the profitability value owned by the Dhomber Air Force Cooperative, Balikpapan, the better the management's performance in generating profits for the company.